ANALYSIS OF INDICATORS OF THE NEUROMUSCULAR APPARATUS AND KINEMATIC CHARACTERISTICS OF THE RUNNING TECHNIQUE OF TRACK AND FIELD ATHLETES OF SPORTS PERSONS WITH INTELLECTUAL DISABILITIES - Krasnoperova T.V.; Lukmanova N.B. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the features of bioelectrical activity and viscoelastic properties of the muscles of the lower extremities in relation to the kinematic characteristics of the 100-meter run technique in athletes with intellectual disabilities. Methods and structure of the study. With the participation of 23 athletes with a mild degree of mental retardation, studies were carried out using non-invasive methods of electromyography, myotonometry and the calculation of the asymmetry coefficient to assess the functional capabilities of the muscles of the lower extremities, indicators were analyzed at rest and during static muscle tension. A video analysis of the 100-meter running technique and a correlation analysis were carried out. Results and conclusions. The features of bioelectrical activity and viscoelastic properties of the muscles of the lower extremities at rest and under static load were revealed. At rest, high values of the amplitude of muscle contraction, asymmetry of the indicators of tone and stiffness of the studied muscle groups on the left are noted. Under static load, muscle asymmetry to the left was revealed, higher functional reserves of the studied muscle groups of the lower extremities on the left were shown. Correlation analysis showed a high degree of interdependence of running technique indicators with bioelectrical activity and stiffness of the studied muscles of the left lower limb.